Characterization of some Indian coals to assess their liability to spontaneous combustion. (1st January 2016) - Nimaje, D.S.; Tripathy, D.P.
Abstract: Mine fires are a major problem in global coal mining industry and most of them are caused by spontaneous combustion that needs proper attention in strategic planning. The operational management must pay attention to an inbuilt system management for timely detection at the initial stage prior to devastating effect. To assess the spontaneous combustion liability of coal, intrinsic properties and susceptibility indices play a vital role. Forty-nine in-situ coal samples were collected from different coalfields of India. Experimentation of the samples was carried out for proximate, ultimate, and petrographic analysis; crossing point temperature; flammability temperature; Olpinski index; wet oxidation potential analysis; and differential thermal analysis to ascertain the proneness of coal to spontaneous combustion. From the statistical analysis of the samples, it was established that the parameters of the ultimate analysis show significant correlation with Olpinski index as compared to other susceptibility indices and, hence, it can be used as a reliable index to assess the susceptibility of Indian coals to spontaneous combustion.